Characterization of Pathogenesis and Inflammatory Responses to Experimental Parechovirus Encephalitis - Jan, Ming-Wei; Su, Hong-Lin; Chang, Tsung-Hsien; Tsai, Kuen-Jer (Frontiers in Immunology, 2021)
Human parechovirus type 3 (PeV-A3) infection has been recognized as an emerging etiologic factor causing severe nerve disease or sepsis in infants and young children. But the neuropathogenic mechanisms of PeV-A3 remain unknown. To understand the pathogenesis of PeV-A3 infection in neuronal system, PeV-A3-mediated cytopathic effects were analyzed in human glioblastoma cells and neuroblastoma cells. PeV-A3 induced interferons and inflammatory cytokines expression in these neuronal cells. The pronounced cytopathic effects accompanied with activation of death signaling pathways of apoptosis, autophagy and pyroptosis were detected. A newly experimental disease model of parechovirus encephalitis was established. In the disease model, intracranial inoculation with PeV-A3 in C57BL/6 neonatal mice showed body weight loss, hindlimb paralysis and approximately 20% mortality. PeV-A3 infection in hippocampus and cortex regions of the neonatal mice brain was revealed. Mechanistic assay supported the in vitro results, indicating detection of PeV-A3 replication, inflammatory cytokines expression and death signaling transduction in mice brain tissues. These in vitro and in vivo studies revealed that the activation of death signaling and inflammation responses were involved in PeV-A3-mediated neurological disorders. The present results might account for some of the PeV-A3-associated clinical manifestations.